A Metastatic Papillary Thyroid Carcinoma Could be Confused Clinically with a Primary Renal Neoplasm; A Case Report and Literature Review - El-Naby, Noha ED Hassab; Mohammed, Maisa Hashem (Asian Pacific Journal of Cancer Biology, 2022)
Background: Papillary thyroid carcinoma is the most common thyroid neoplasm. It has a very high incidence of regional lymph node metastasis at the initial presentation. However, vascular spread is a very uncommon event. Lungs and bones are the most frequent sites of vascular metastasis from papillary thyroid carcinoma. Case concerns: The currently discussed case was obtained from the archive of Pathology laboratory, Sohag University. A 46-year-old female patient admitted to Urology Department, Sohag University, in 2015. The patient had a left loin pain, no other clinical data included in her referral sheet . Radiological findings revealed a renal mass and left radical nephrectomy was performed. Histopathological evaluation revealed a circumscribed neoplasm, formed of densely packed acini with scanty stroma. The patient was diagnosed as renal oncocytoma. On re-evaluation of the Hematoxylin and Eosin-stained slides; the nuclear features were different from those described in renal oncocytomas. So, a panel of immunohistochemical markers was performed (anti-CK7, anti-EMA, anti-Vimentin, anti-Thyroglobulin and anti-TTF1). Results: The neoplastic cells showed strong and diffuse cytoplasmic expression for Thyroglobulin and CK7 and nuclear expression for TTF1. The neoplastic cells didn’t express EMA or Vimentin. Based on the characteristic nuclear features detected by Hematoxylin and Eosin-stained slides and the obtained immunohistochemical results; the diagnosis of metastatic papillary thyroid carcinoma to the kidney was confirmed. Conclusions: Papillary thyroid carcinoma may metastasize to the kidney and form a solitary mass, that could be confused as a primary renal neoplasm.